Multiple indices on different habitats and descriptors provide consistent assessments of environmental quality in a marine protected area - Oprandi, Alice; Atzori, Fabrizio; Azzola, Annalisa; Bianchi, Carlo Nike; Cadoni, Nicoletta; Carosso, Lara; Desiderà, Elena; Frau, Francesca; Garcia Gutiérrez, Maria Leonor; Guidetti, Paolo; Morri, Carla; Piazzi, Luigi; et al. (Frontiers in Marine Science, 2023)
In the last decades, climate change and human pressures have increasingly and dramatically impacted the ocean worldwide, calling for urgent actions to safeguard coastal marine ecosystems. The European Commission, in particular, has set ambitious targets for member states with two major directives, the Water Framework Directive (WFD) and the Marine Strategy Framework Directive (MSFD), both designed to protect the marine environment in EU waters. Diverse biotic indices have accordingly been developed to assess water and habitat quality. The WFD adopts four Biological Quality Elements (BQEs), whereas the MSFD recommends a set of eleven qualitative descriptors. The borderline between water quality and habitat quality is hard to trace and so far most assessments have involved the use of a few indices and were mainly related to a single BQE or qualitative descriptor. In this study, thanks to the availability of a large dataset encompassing a wide array of descriptors, we compared the performance of 11 biotic indices relative to three habitats/biotic components (reefs, seagrass, and fish) of the Marine Protected Area (MPA) of Capo Carbonara (SE Sardinia, Italy). The aim was to assess whether the indices were consistent in defining the environmental status in the MPA investigated. We used the graphical approach RESQUE (REsilience and QUality of Ecosystem), which enabled us to obtain a single and comprehensive measure of the status of the environment by integrating several metrics. This approach was applied here to different habitats for the first time. All indices were consistent with each other in confirming the good status of Capo Carbonara MPA. The use of RESQUE provided insights to interpret the differences between water quality, defined according to the WFD, and habitat quality, defined according to the MSFD. Differences between the two EU directives, in terms of either requirements or goals, have long been discussed but the present study highlights for the first time that they are congruent in their assessment of the environmental status of marine ecosystems.